Estrogen Therapy and Bone Mineral Density in African-American and Caucasian Women - Eskridge, Susan L. (Oxford University Press, 2010)
Controlling for body size and composition, the authors examined the association between estrogen therapy and bone mineral density in older African-American and Caucasian women. In 1992–1998, 443 African-American and 989 Caucasian women aged 45–87 years were assessed for medication use, laboratory variables, behavioral characteristics, and bone mineral density. The mean age was 61.3 (95% confidence interval: 60.3, 62.3) years in African Americans and 71.0 (95% confidence interval: 70.4, 71.7) years in Caucasians (P < 0.001). All measures of body size and composition were significantly greater in the African-American women compared with Caucasian women (P < 0.001). As expected, African Americans had significantly higher bone mineral density at all 4 sites independent of age, weight, body composition, estrogen use, and lifestyle factors. Although Caucasians were significantly more likely to currently use estrogen (48.9% vs. 33.9%; P < 0.001), African Americans not using estrogen had significantly higher bone mineral density at all sites except the spine than Caucasians who were using estrogen. Regression models including age and lean mass explained the most variation in bone mineral density (R(2) range = 0.13–0.37). Results suggest that higher levels of bone mineral density in African-American women were not due to estrogen use.